The role of DARPP-32 in breast cancer progression - Saidy, Behnaz (2022)
Breast cancer accounts for one in every eight females with cancer, and it is the fifth most common cause of cancer death. Previously, our group demonstrated that low expression of DARPP-32 is associated with adverse breast cancer specific survival. The principle aim of this study is to explore the role of DARPP-32 in breast cancer progression.